Cancer incidence in adults living in the vicinity of nuclear power plants in France, based on data from the French Network of Cancer Registries. Issue 5 (3rd November 2017) - Desbiolles, Alice; Roudier, Candice; Goria, Sarah; Stempfelet, Morgane; Kairo, Cécile; Quintin, Cécile; Bidondo, Marie‐Laure; Monnereau, Alain; Vacquier, Blandine
Abstract : Nuclear power plants (NPPs) release toxic emissions into the environment that may affect neighboring populations. This ecologic study was designed to investigate the possibility of an excess incidence of cancer in the vicinity of French NPPs by examining the incidence by municipality of 12 types of cancer in the population aged 15 years and older during the 1995–2011 period. Population exposure to pollution was estimated on the basis of distance from towns of residence to the NPP. Using regression models, we assessed the risk of cancer in a 20‐km zone around NPPs and observed an excess incidence of bladder cancer (Relative Risk (RR), 95% Credibility Interval (95% CI)) in men and women (RRmen  = 1.08; 95% CI: 1.00, 1.17 and RRwomen  = 1.19; 95% CI: 1.02, 1.39). Women living within the 20‐km proximity areas had a significantly reduced risk of thyroid cancer (RRwomen  = 0.86; 95% CI: 0.77, 0.96). No excess risk of hematologic malignancies in either sex was seen. The higher than expected incidence of bladder cancer may be due to an excess incidence localized around the Flamanville NPP and the nearby La Hague nuclear waste treatment center, which is a source of chemical contaminants, many (including arsenic) of them known risk factors for bladder cancer. Differences in medical practices could explain the reduced risk of thyroid cancer. In this first study of adults living near NPPs in France, cancer incidence is significantly higher than in the references populations for one of the cancer types studied: bladder cancer. Abstract : What's new? Potential health effects associated with living near nuclear power plants (NPPs) are a subject of widespread concern in France, which has the second‐highest number of civil nuclear installations worldwide. Here, incidence of solid cancers and hematologic malignancies was estimated over the period 1995–2011 for populations within a 20‐km radius of six French NPPs. Excess mortality from bladder cancer was observed for both men and women, while women had significantly reduced mortality rates from thyroid cancer. The higher‐than‐expected increase in bladder cancer incidence may be attributed to a nuclear waste treatment center that is sources of chemical contaminants associated with bladder cancer risk.